Loan guarantee schemes for SMEs – the experience in Malaysia - Boocock, Grahame (Practical Action Publishing, 1996)
Government-backed loan schemes have been introduced in many countries to enable SMEs to have access to funding at a reasonable cost. This article evaluates the schemes offered in Malaysia by the Credit Guarantee Corporation (CGC).Three key areas are explored: the relationship between small firms, banks and the CGC; the level of finance additionality in evidence; and the level of economic additionality generated.In each of these areas, the CGC's effectiveness in meeting the needs of SMEs, banks and the wider economy appears to have been limited.A new scheme introduced by the CGC is then described and the question is asked whether this scheme will enable the CGC to achieve its objectives, notably a greater degree of financial and economic additionality. Finally, the implications of the CGC's experience for other developing countries are summarized.